Strafferetlig forfølgelse af menneskehandel til prostitution i Danmark: Hvilken retsbeskyttelse får ofrene? - Annick Prieur (Nordisk Tidsskrift for Kriminalvidenskab)
Abstracts This article asks what victims of human trafficking for prostitution get out of prosecution in Denmark. An analysis of all cases reported to the police over a 5-year period shows that they are very few in number, and that most of the reported cases are closed without prosecution for trafficking. Compared to Danish authorities’ registration of 363 persons possibly trafficked for prostitution in the same period, 37 possible victims (in 16 different cases) were reported to the police, and 25 of the 37 obtained a conviction of their traffickers (in all 18 persons convicted). Only two victims received some economic compensation. More resources allocated to the area would almost certainly have led to more cases being prosecuted. Victim collaboration is essential for proper investigation and prosecution. Yet collaboration may be difficult to achieve as long as prosecution and conviction do not provide victims with compensation, protection or permanent Dansih residency.